Private Sector Investment on Renewable Energy Utilization in Developing Countries - Aslani, Alireza (Journal of Technology Innovations in Renewable Energy, 2013)
Feasibility potentials in the Middle East and Iran offer many opportunities for private sector investment in renewable energy industry. However, due to the high primary investment costs in this technology, as well as dominate role of fossil fuels in the Middle East, promotion plans cannot be achieved without government incentives and supports. First, this article tries to answer to one of the main questions of private investors related to identification of the most important renewable source for investment in Iran. Then, to success implementation of investment and government plans, different polices and support schemes of the Nordic countries as successful countries in adoption of renewables are reviewed and discussed.